Asuhan Keperawatan Komprehensif Pada An. F Dengan Diagnosa Medis Diare di Wilayah Kerja Puskesmas Kalikajar - Galand Okvadwiarko; Eko Sari Ajiningstyas; Sudiarto S (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Background : The frequency of diarrhea in children in Central Java was 8.4% in 2018, according to the diagnosis of health workers (Riskesdas, 2018). Diarrhea is a condition of abnormal or uncharacteristic stool output characterized by an increase in volume, liquid stool, and frequency of defecation more than 3 times a day. Purpose: Find out comprehensive nursing care for children with a medical diagnosis of diarrhea. Methods: This research uses a case study method with male respondents with a medical diagnosis of diarrhea. Data collection techniques were carried out by interview (the results of the interview contained client identity, main complaints, history of current and past illnesses), observation and physical examination. This research was conducted at work area of the Kalikajar Health Center for 3 days (May 29, 2023 until May 31, 2023). Results: The results of case studies in children with diarrhea obtained diagnoses that is, diarrhea, hyperthermia and hypovolemia. After carrying out nursing care for 3 days, it was found that the three problems were resolved so that the intervention was stopped. Conclusion : . Based on the evaluation results, the problems of diarrhea,hyperthermia and hypovolemia in children can be resolved. Keywords: Children, Diarrhea, Nursing care.